Spatial and statistical analysis of burned areas with Landsat-8/9 and Sentinel-2 satellites: 2023 Çanakkale forest fires - Bitek, Deniz; Sanli, Fusun Balik; Erenoglu, Ramazan Cuneyt (SPRINGER, 2024)
Forest fires are one of the most dangerous disasters that threaten the natural environment, life, and diversity worldwide. The frequency of these fires and the size of the impact area have been increasing in recent years. Remote sensing methods are frequently used to detect areas affected by forest fires, to map the burned areas, to follow the course of fires, and to reveal verious statistical data. In this study, forest fires that occurred on 16.07.2023 and 22.08.2023 in & Ccedil;anakkale province were analyzed using Landsat-8/9 and Sentinel-2 satellite images and various remote sensing indices. By using the images before and after the fires, the burned areas were determined and the performance of different indices were compared. The areas affected by fires were revealed using dNBR (Differenced Normalized Burn Ratio), RBR (Relative Burn Ratio), and dNDVI (Differenced Normalized Difference Vegetation Index) indices. The fire-affected areas were calculated as 3,244.41 hectares (ha) and 4,292.37 ha for the July and August fires with Landsat-8/9 images, respectively; and 3,312.08 ha and 4,445.03 ha with Sentinel-2 images, respectively. In addition, the accuracy analysis of the areas calculated using different indices was performed. By comparing the results of the analysis and accuracy assessment, the performances of Landsat-8/9 and Sentinel-2 images were determined. According to the results obtained, the Overall Accuracy values of the areas affected by fires were between 0.76 - 0.89, Kappa statistical values were between 0.52 - 0.78, and the highest value in the calculation of the burned areas was the dNBR index for both Landsat-8/9 and Sentinel-2 images.
Keywords: Forest fire; & Ccedil; anakkale; Satellite imagery; Burnt area mapping; Spectral indices; SEVERITY; PERFORMANCE; Environmental Sciences & Ecology